(untitled) - Mackey, Daphne (Oxford, 2007)
Panorama: Building Perspective Through Listening offers a series of high-interest, listening selections related to academic subjects. Each unit contains three thematically linked listening texts-the first on a person, the second on a related place, and the third on a related concept or event. Each unit in Panorama Listening correlates to the corresponding unit in Panorama Reading. The two strands can be used separately, or together for maximum exploration of content and development of critical thinking skills
Keywords: English language,Anh ngữ thực hành; textbooks for foreign speakers,Tài liệu dùng cho người nước ngoài